THE THEORETICAL FOUNDATIONS OF VIBRATION DAMPERS BY ROLLING FRICTION - Bondarenko, L. M.; Yakovlev, S. A.; Kramar, I. E.; Shaptala, A. I. (Science and Transport Progress, 2015)
Purpose. There are some unresolved issues in vibration damping – the lack of engineering calculations for the vibration dampers by rolling friction; the absence of evidence of their application appropriateness. Considering this fact, the authors suggest to prove that the dampers based on rolling friction, are similar in rate of oscillation damping by hydraulic shock absorbers. At the same time, they are easier for the hydraulic design, and easily amenable to manual adjustment, both in automatic and manual mode. Methodology. Fixed techniques of practice in order to determine amplitudes of the oscillations of a shock absorber led to a predetermined result and will apply this theory in the calculation of other vibration dampers. Findings. Analysis of the formulas and graphs leads to the following conclusions and recommendations: 1) the nature of the oscillation damping at vibration dampers by rolling friction is close to their decay in the viscous resistance; 2) when conducting the necessary experiments the shock absorber rolling can be recommended as alternatives to hydraulic ones. The research results of this task will help implement the new trend in reduction of dynamic loads in vehicles. Originality. With the help of theoretical curves to determine the coefficients of rolling friction the dependences for determining the amplitudes of the oscillations in the vertical movement of cargo were obtained. At the same time, the previously proposed analytical dependence for determining the coefficient of rolling friction contains only conventional mechanical constants of the contacting bodies and there geometrical dimensions. Practical value. Due to the existing well-known disadvantages of hydraulic shock absorbers it would be logical to apply shock absorbers that are technologically convenient in manufacturing and easy to adjust the damping rate. The proposed theory can be used in the design of shock absorbers rolling as an alternative to the hydraulic shock absorbers of machines.